Mitochondria Rich-Cells Localization and Effect of Salinity on their Distribution in Kidney Tubules of Persian Sturgeon Acipenser persicus - S. Mosafer Khorjestan; S. Khodabandeh; Z. Khoshnood (Cell Journal, 2009)
Objective: The urinary system of euryhaline fish, as well as the gills, is involved inion regulation through the production of dilute urine in freshwater and isotonic urinein seawater. The low osmolality of the urine originates from an active reabsorptionof ions by Ionocytes or mitochondria rich-cells (MRCs) present in certain parts of theurinary system. Mitochondria rich-cells possess a high density of Na+, K+-ATPase.Materials and Methods: Persian Sturgeon fry’s, adapted to freshwater and dilutedCaspian Sea water (‰5 salinity) were fixed in Bouin’s solution after 24h. After thehydration with ethanol, the samples were paraffinaized and sectioned. Light microscopyand Hematoxiline-Fushin staining were used for histological examinations.Immunolocalization of Na+, K+-ATPase was observed through fluorescent microscopy(450-490 μm), using IgGα5 (as primary antibody) and FITC (as secondaryantibody).Results: In both experimental conditions, maximum immunofluorescence of Na+,K+-ATPase (in mitochondria rich-cells) was found in distal and collective tubules. Inboth ureter and urinary bladder, immunostainings were found in dispersed cells withrelatively weak intensity. In ‰5 acclimated fish, weak immunofluorescence was alsoobserved in neck segment and proximal tubules, as well as in distal and collectivetubules.Conclusion: Alternation in mitochondria rich-cells and Na+, K+-ATPase distributionin kidney tubules of ‰5 acclimated fry’s showed that the blood and osmolytes werenearly isotonic to environment but not isoionic. Thus the fish needs the absorptionand excretion of some ions for the body homeostasis and osmoregulation.